Perancangan Program Pendampingan Lanjut Usia Berbasis Home Care Di Posbindu Kelurahan Geger Kalong - Nurfatimah, Rosita; Sulastri, Melly Sri; Jubaedah, Yoyoh (FamilyEdu: Jurnal Pendidikan Kesejahteraan Keluarga, 2017)
This research is motivated that existing programs in Posbindu Miana VIII village Geger Kalong limited medical examination and gymnastics, while for assisting the elderly based Home Care program there has been no structured and systematic, where as the elderly who are outside the home still need assistance, especially from the family and community environment. The purpose of this study to generate elderly assistance program based Home Care in Posbindu the village Geger Kalong. This study uses a method of Research and Development with Model Addie which include Analysis, Design, Development, Implementation and Evaluation. Participants in this study using purposive sampling, where selected families who provide active assistance to the elderly. Identification of needs through open interviews to the 12 families of elderly and four cadres Posbindu. The program is designed consists of program components: objectives, goals, forms of assistance, organizing institutions and implementing the program, besides, program modules include assisting the elderly. Form of assistance theÂ  elderly cover physical, social, mental and spiritual. Expert judgment program conducted by academics and practitioners elderly service agencies. Repairs done by the revised program and developed according to feedback from the validator. Trials program that has been revised and expanded to do a non potential grandmother was 80 years old. These trials were conducted by the companion of the family environment and the companion Posbindu Miana VIII RW. 08 village Geger Kalong. Recommended for families and the elderly Posbindu, the program can be implemented to meet the various needs of the elderly. For the elderly should introspect, especially in the health and follow the advice recommended by related parties. For further research the elderly assistance program based Home Care can be developed or modified according to the needs of research.